Pengukuran Kinerja Keuangan Koperasi Dengan Pendekatan Rasio (Studi Pada Koperasi Osseda Faolala Perempuan Nias 2019-2022) - Aferiaman Telaumbanua; Peringatan Harefa (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
The purpose of this research is to determine the financial performance of the Nias Women's Osseda Faolala Consumer Cooperative (K-OFPN) in Gunungsitoli City in 2019 – 2022 using the profitability ratio, liquidity ratio and solvency ratio approach. In this study using a type of quantitative descriptive research, namely a series of activities starting from data collection, processing and interpretation or interpreting it using financial formulas so that it can provide a clear picture of the situation under study, while the data used in this study are financial report data. from 2019-2022. The results of the analysis of the financial performance of the Nias Women's Osseda Faolala Consumer Cooperative (K-OFPN) using the financial ratio analysis approach are quite good, but improvements are still needed in terms of financial management.